371 How Do Case Type, Length of Stay, and Comorbidities Affect Medicare Diagnosis-Related Group Reimbursement for Minimally Invasive Surgery for Deformity?. (August 2016) - Nunley, Pierce D.; Fessler, Richard G.; Park, Paul; Zavatsky, Joseph M.; Mundis, Gregory M.; Uribe, Juan S.; Eastlack, Robert; Nguyen, Stacie; Chou, Dean; Wang, Michael Y.; Anand, Neel; Kanter, Adam S.; et al.
Abstract : INTRODUCTION: We investigated Medicare diagnosis-related group (DRG)-based reimbursement for minimally invasive surgery (MIS) deformity procedures in our study group hospitals based on length of stay and presence of comorbid conditions (CC). METHODS: DRG-based reimbursement was obtained for MIS anterior, posterior, and circumferential 1-level and multilevel fusion for listhesis and deformity cases with and without CC from 12 institutions throughout the United States. The 3 most common MIS procedures were analyzed to compare reimbursement based on DRG coding: (1) fusion via anterior or posterior only; (2) fusion anterior with fixation posterior percutaneous (no dorsal fusion); and (3) fusion combined anterior and posterior. RESULTS: The number of levels fused does not affect the reimbursement for all cases. Cases 1 and 2 without CC, 3-day stay reimbursed 41 404 vs 8-day reimbursed 42 808. Cases 1 and 2 with CCs, 3-day stay reimbursed 54 476 vs 8-day stay reimbursed 55 881. Case 3 without CC, 3-day stay reimbursed 47 992 vs 8-day stay reimbursed 49 397. Case 3 with CC, 3-day reimbursed 61 806 vs 8-day reimbursed 63 212. The increased payment for an 8-day stay was 1405 or 281 per day. If a deformity case 1 or 2 is coded incorrectly as a degenerative case the decrease in payment was 9769 lower (−24%) with no CC and 22 841 lower (−42%) with CC. CONCLUSION: Regardless the direct costs, Medicare DRG-based reimbursement was the same for single and multilevel MIS deformity cases. The use of posterior percutaneous fixation without dorsal fusion resulted in a 13% to 16% lower reimbursement compared with the addition of a posterior arthrodesis. Coding a deformity case as degenerative by the hospital resulted in 24% to 42% lower DRG-based reimbursement. In today's challenging environment it is important that physicians and hospitals better understand procedure and coding issues in order to be able to continue to offer complex spinal surgeries cost-effectively to our patients.